Green project work for process writing amidst the pandemic: Planning, implementing, and reflections - Lestari Setyowati; Sari Karmina; Sony Sukmawan; Razlina Razali (Fakultas Sastra Universitas Negeri Malang, 2022)
Green project work for process writing amidst the pandemic: Planning, implementing, and reflectionsThe aims of this paper are to discuss the concepts underlying Project-based learning (PjBL) and its syntax and to explore the planning, implementation, and reflection of PjBL in the online teaching of writing a process paragraph on the topic of using Reduce, Reuse, and Recycle (3R) principles to save the environment. Thirty-one students joined the paragraph writing course. The learning process and the students’ products of their projects were collected and documented in the form of videos, Power Point presentation, and electronic writing portfolios. The paper discusses how PjBl promotes collaborative work, problem-solving, critical thinking and technology integration. It also illustrates the steps of the implementation of PjBL which include planning, implementing, and reflecting. The project products were the students’ compositions and the videos showing the process in how to do or to make something that reflect the 3R principles. The majority of the students’ compositions were in ‘very good’ criteria, and the students’ videos were published in YouTube. The implementation of PjBL in the online teaching of process writing on the environmental topic increases the students’ critical thinking and creativity in solving global problems.Proyek Hijau untuk menulis paragraf proses di tengah pandemi: Perencanaan, pelaksanaan, dan refleksiTujuan artikel ini adalah membahas konsep yang mendasari pembelajaran berbasis proyek (PjBL) dan sintaksnya, dan mengeksplorasi perencanaan, pelaksanaan, dan refleksi PjBL dalam pembelajaran online menulis paragraf proses dengan topik menggunakan prinsip-prinsip Reduce, Reuse, dan Recycle (3R) untuk menyelamatkan lingkungan. Ada 31 mahasiswa yang mengikuti kelas menulis paragraf. Semua proses belajar mahasiswa dan produk proyek mereka dikumpulkan dan didokumentasikan dalam bentuk video, presentasi Power Point, dan portofolio tulisan elektronik. Artikel ini membahas bagaimana PjBl mengedepankan kerja kolaboratif, pemecahan masalah, integrasi teknologi, dan berpikir kritis. Artikel ini juga mengilustrasikan langkah-langkah implementasi PjBL yang meliputi perencanaan, pelaksanaan, dan refleksi. Produk proyek adalah karya mahasiswa dan video yang menunjukkan proses bagaimana melakukan atau membuat sesuatu yang mencerminkan prinsip 3R. Sebagian besar tulisan mahasiswa termasuk dalam kriteria 'sangat baik', dan video mahasiswa telah dipublikasikan di YouTube. Penerapan PjBL dalam menulis paragraph proses bertema lingkungan meningkatkan daya pikir kritis dan kreativitas siswa dalam memecahkan masalah ekologi global.